OCA optical glue, preparation method thereof and OCA optical tape
The OCA optical glue prepared by specific ratios of chemical components and photopolymerization solves the problem that existing OCA glue is difficult to take into account low dielectric constant and good fluidity, and achieves efficient touch panel performance and efficiency.
Patent Information
- Application Number
- CN202510102334.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
When existing OCA glue improves adhesiveness and fillability, it is difficult to take into account low dielectric constant and good fluidity, which affects the working performance and touch efficiency of the touch panel.
By combining a specific ratio of alkyl acrylate and its derivatives, nitrogen-containing monomers, hydroxyl-containing monomers, pre-concentration initiators, chain transfer agents, coated photoinitiators and dual-compartment crosslinking agents, OCA optical glue is prepared by photopolymerization to control the dielectric constant and increase the energy storage modulus.
It realizes the low dielectric constant, good fluidity, adhesiveness and anti-aging performance of OCA optical glue, and improves the working performance and touch efficiency of the touch panel.
Smart Images

Figure CN119912879A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical adhesives, and in particular relates to an OCA optical adhesive, a preparation method thereof and an OCA optical adhesive tape. Background Art
[0002] In recent years, the progress and development of the display market has made the combination of image display devices such as mobile phones and tablets and touch screen panels gradually popular in people's lives. With the development of the electronics market, in addition to mobile phones, more and more laptops have begun to add touch functions, and the requirements for touch sensitivity are also higher.
[0003] OCA full bonding technology enables the polarizer or transparent conductive film (ITO film) in the LCD screen or other electrostatic capacitive touch panel to seamlessly connect with the LCD display module or other substrates such as glass, so that the display effect and touch effect of the screen reflection image are further enhanced. OCA glue is usually used to bond glass plates and modules in electrostatic capacitive touch panels. In order to ensure the working needs and touch efficiency of the touch panel, OCA glue is required to have low dielectric, high step filling, high adhesion, high durability and other properties. Especially when touching, the delay time of the output signal of the corresponding position when touching with a finger or other means needs to be extremely short. Therefore, the low dielectric property of OCA glue is very important.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The object of the present invention is to provide an OCA optical glue which has a low dielectric constant and has good fluidity, adhesion and filling properties.
[0006] In order to achieve the above-mentioned purpose, a technical solution provided by a specific embodiment of the present invention is as follows: an OCA optical glue, whose components, measured by weight percentage, include: 82%-89% of alkyl acrylates with 4-21 carbon atoms and their derivatives: 8%-15% of nitrogen-containing monomers; 1.5%-1.6% of hydroxyl-containing monomers; 0.04%-0.15% of pre-polymerization photoinitiator; 0.17%-0.2% of chain transfer agent; 0.19%-0.20% of coating photoinitiator; 0.14%-0.15% of difunctional cross-linking agent; the sum of the weight percentages of the components is 100%.
[0007] In one or more embodiments of the present invention, the alkyl acrylate and its derivatives are selected from one or more of alkyl acrylates having a straight chain, alkyl acrylates having a branched alkyl chain, alkyl methacrylates having a straight chain, and alkyl methacrylates having a branched alkyl chain.
[0008] In one or more embodiments of the present invention, the alkyl acrylate and its derivatives are selected from one or more of undecyl methacrylate, isooctyl methacrylate, 2-ethylhexyl acrylate, heptadecanyl methacrylate, isostearyl acrylate and isobornyl acrylate.
[0009] In one or more embodiments of the present invention, the alkyl acrylate and its derivatives are a combination of 2-ethylhexyl acrylate, isostearyl acrylate and isobornyl acrylate.
[0010] In one or more embodiments of the present invention, the nitrogen-containing monomer is selected from one or more of N,N-dimethylformamide, N-methylsuccinamide, N,2,3-trimethyl-2-isopropylbutyramide, N,N-dimethylacrylamide, 1,1-cyclohexyldiacetic acid monoamide, acrylamide, N-vinylcaprolactam, acrylonitrile, N-vinylpyrrolidone, phenoxyethyl methacrylate, triethylene glycol dimethacrylate and 4-hydroxyvinyloxybenzophenone methacrylate.
[0011] In one or more embodiments of the present invention, the nitrogen-containing monomer is a combination of N-vinyl pyrrolidone, acrylamide and 4-hydroxyvinyloxybenzophenone methacrylate.
[0012] In one or more embodiments of the present invention, the hydroxyl-containing monomer is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, hydroxypropyl methacrylate and 2-carboxyethyl acrylate.
[0013] In one or more embodiments of the present invention, the pre-polymerization photoinitiator is selected from one of 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and / or, the chain transfer agent is selected from one of n-dodecyl mercaptan, isooctyl thioglycolate and 2-mercaptoethanol; and / or, the coating photoinitiator is selected from one of isopropyl ferrocenium hexafluorophosphate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone; and / or, the bifunctional cross-linking agent is selected from one of 1,6-ethylene glycol diacrylate, N,N-methylenebisacrylamide and tripropylene glycol diacrylate.
[0014] The technical solution provided by another specific embodiment of the present invention is as follows: a method for preparing an optical glue of the above-mentioned OCA optical glue, which comprises: heating an alkyl acrylate and its derivatives, a nitrogen-containing monomer, a hydroxyl-containing monomer, a pre-polymerization photoinitiator and a chain transfer agent in a water bath, introducing nitrogen, removing oxygen and stirring to obtain a first mixture; continuing to introduce nitrogen into the first mixture, stirring and irradiating with a UV lamp for photoinitiation to raise the temperature to 30°C-35°C; stirring in the dark and cooling to room temperature to obtain a pre-polymerized glue with a solid content mass fraction of 30%-35%; adding a coating photoinitiator and a bifunctional cross-linking agent to the pre-polymerized glue, stirring in the dark and degassing under reduced pressure to obtain the OCA optical glue.
[0015] Another specific embodiment of the present invention provides a technical solution as follows: an OCA optical adhesive tape, comprising: a light release film, a heavy release film and an OCA optical adhesive layer. The thickness of the light release film is 40 μm-60 μm; the thickness of the heavy release film is 70 μm-90 μm; the OCA optical adhesive layer is coated between the light release film and the heavy release film using the above-mentioned OCA optical glue.
[0016] Compared with the prior art, the OCA optical glue and OCA optical tape of the present invention adopt the above formula and control the ratio to reduce the dielectric constant of the OCA optical glue, and at the same time improve the room temperature and low temperature storage modulus of the OCA optical glue, so that the OCA optical glue itself shows good flow properties, which is conducive to step filling. In addition, the OCA glue also has good anti-aging performance, light transmittance and adhesion. The preparation method of the OCA optical glue of the present invention adopts a photopolymerization method with simple steps, which is suitable for industrial production, and the dielectric constant, light transmittance, adhesion and anti-aging performance of the prepared OCA optical glue are more comprehensive. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 The figure is a flow chart of a method for preparing OCA optical glue in one embodiment of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0020] An OCA optical glue in one embodiment of the present invention comprises, by weight percentage, 82%-89% of alkyl acrylates having 4-21 carbon atoms and their derivatives: 8%-15% of nitrogen-containing monomers; 1.5%-1.6% of hydroxyl-containing monomers; 0.04%-0.15% of pre-polymerization photoinitiator; 0.17%-0.2% of chain transfer agent; 0.19%-0.20% of coating photoinitiator; 0.14%-0.15% of bifunctional crosslinking agent; the sum of the weight percentages of the above components is 100%.
[0021] In the above-mentioned embodiment, the OCA optical glue of the present invention is obtained by polymerization of alkyl acrylates having 4 to 21 carbon atoms and their derivatives, and has a lower dielectric constant, thereby being able to effectively reduce the capacitance effect in the circuit.
[0022] In one embodiment, the alkyl acrylate and its derivatives are selected from one or more of alkyl acrylate with a straight chain, alkyl acrylate with a branched alkyl chain, alkyl methacrylate with a straight chain, and alkyl methacrylate with a branched alkyl chain. The aforementioned alkyl acrylate and its derivatives have the effects of improving adhesion, chemical corrosion resistance, weather resistance and high light transmittance. The network structure formed by the polymerization and cross-linking of the alkyl acrylate as the main molecular structure of the OCA optical adhesive of the present invention can effectively improve the stability and reliability of the bonded electronic equipment.
[0023] Further, the alkyl acrylate and its derivatives are selected from one or more of undecyl methacrylate, isooctyl methacrylate, 2-ethylhexyl acrylate, heptadecanyl methacrylate, isostearyl acrylate and isobornyl acrylate.
[0024] Preferably, the alkyl acrylate and its derivatives are a combination of 2-ethylhexyl acrylate, isostearyl acrylate and isobornyl acrylate.
[0025] In one embodiment, the weight percentages of 2-ethylhexyl acrylate, isooctadecyl acrylate and isobornyl acrylate in the OCA optical adhesive are 30%-35%, 30%-35% and 16%-18% respectively. By using the aforementioned alkyl acrylates and their derivatives and controlling their proportions, the OCA optical adhesive has higher viscosity, better fluidity and lower dielectric constant.
[0026] In one embodiment, the addition of nitrogen-containing monomers increases the interaction between molecules and the bonding substrate, increases the cohesive strength, can significantly improve the adhesion of OCA optical adhesives and maintain a relatively low room temperature and high temperature storage modulus and good creep performance. Further, the nitrogen-containing monomer is selected from one or more of N,N-dimethylformamide, N-methylsuccinamide, N,2,3-trimethyl-2-isopropylbutyramide, N,N-dimethylacrylamide, 1,1-cyclohexyldiacetic acid monoamide, acrylamide, N-vinyl caprolactam, acrylonitrile, N-vinyl pyrrolidone, phenoxyethyl methacrylate, triethylene glycol dimethacrylate and 4-hydroxyvinyloxybenzophenone methacrylate.
[0027] Preferably, the nitrogen-containing monomer is a combination of N-vinyl pyrrolidone, acrylamide and 4-hydroxyvinyloxybenzophenone methacrylate.
[0028] Specifically, the weight percentages of N-vinyl pyrrolidone, acrylamide and 4-hydroxyvinyloxybenzophenone methacrylate in the OCA optical adhesive are 6%-8%, 6%-9% and 0.5%-0.7%, respectively.
[0029] In one embodiment, the hydroxyl-containing monomer is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, hydroxypropyl methacrylate and 2-carboxyethyl acrylate. The hydroxyl-containing monomer has the function of increasing the interaction between molecules and the bonding substrate, increasing the cohesive strength through hydrogen bonding between hydroxyl groups, and further improving the optical properties of the OCA optical glue by reducing the cloud point through hydrophilic hydroxyl groups. It can increase the crosslinking degree of the OCA optical glue, form a stronger chemical bond, and maintain high light transmittance during the curing process of the glue. However, due to the high polarity of the hydroxyl monomer molecule, the addition will increase the dielectric constant of the OCA, and its addition amount should be controlled.
[0030] In one embodiment, the pre-polymerization photoinitiator is selected from one of 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0031] The chain transfer agent is selected from one of n-dodecyl mercaptan, isooctyl thioglycolate and 2-mercaptoethanol.
[0032] The coating photoinitiator is selected from one of cumene ferrocenium hexafluorophosphate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone.
[0033] The bifunctional crosslinking agent is selected from one of 1,6-ethylene glycol diacrylate, N,N-methylenebisacrylamide and tripropylene glycol diacrylate.
[0034] like Figure 1 As shown, a method for preparing OCA optical glue in another embodiment of the present invention includes: steps S1-S4.
[0035] Step S1: heating the alkyl acrylate and its derivatives, the nitrogen-containing monomer, the hydroxyl-containing monomer, the pre-photoinitiator and the chain transfer agent in a water bath, introducing nitrogen, removing oxygen and stirring to obtain a first mixture.
[0036] Step S2: Continue to introduce nitrogen into the first mixture, stir and irradiate with a UV lamp to light-initiate the temperature rise to 30°C-35°C.
[0037] Specifically, in step S2, the UVA band light intensity of the UV lamp is 0.699 mW / cm 2 .
[0038] Step S3: Cooling to room temperature with stirring in a dark environment to obtain a prepolymerized glue having a solid content of 30% to 35% by mass;
[0039] Step S4: adding a coating photoinitiator and a bifunctional cross-linking agent to the prepolymerized glue, stirring in the dark, and degassing under reduced pressure to obtain an OCA optical glue.
[0040] In another embodiment of the present invention, an OCA optical adhesive tape comprises a light release film, an OCA optical adhesive layer and a heavy release film in sequence. The thickness of the light release film is 40 μm-60 μm; the thickness of the heavy release film is 70 μm-90 μm; and the OCA optical adhesive layer is coated between the light release film and the heavy release film using the above-mentioned OCA optical glue.
[0041] The present invention is further described below in conjunction with specific embodiments and comparative examples.
[0042] Example 1
[0043] Step S1: 34 parts by mass of 2-ethylhexyl acrylate (2-EHA), 15 parts by mass of isobornyl acrylate (IBOA), 35 parts by mass of isooctadecyl acrylate (ISTA), 1 part by mass of hydroxybutyl acrylate (HBA), 7 parts by mass of N-vinyl pyrrolidone (NVP), 8 parts by mass of acrylamide (AM), 0.6 parts by mass of 4-hydroxyvinyloxybenzophenone methacrylate (ABP), 0.175 parts by mass of n-dodecyl mercaptan (n-DDM), and 0.15 parts by mass of 1-hydroxycyclohexyl phenyl ketone (184) are heated in a water bath, nitrogen is introduced, oxygen is removed and stirred for 30 minutes to obtain a first mixture.
[0044] Step S2: Continue to introduce nitrogen into the first mixture, stir and use UVA band light with an intensity of 0.699 mW / cm 2 The temperature was raised to 30 °C by UV light irradiation.
[0045] Step S3: stirring in the dark, cooling to room temperature, and obtaining a prepolymerized glue having a solid content of 30% by mass;
[0046] 0.2 parts by mass of cumene ferrocenium hexafluorophosphate (651) and 0.15 parts by mass of 1,6-ethylene glycol diacrylate (HDDA) were added to the prepolymerized glue, stirred for 30 minutes in a dark environment and degassed under reduced pressure to obtain OCA optical glue.
[0047] The above OCA optical adhesive was coated between a 50 μm light release film and a 75 μm heavy release film, and the UV curing energy was 1200 mJ to obtain a sheet of OCA optical tape with a thickness of 200 μm.
[0048] Example 2
[0049] On the basis of Example 1, the amount of NVP was adjusted to 5 parts by mass, the amount of AM was adjusted to 10 parts by mass, and the amount of n-DDM was adjusted to 0.2 parts by mass.
[0050] Example 3
[0051] On the basis of Example 1, the amount of n-DDM was adjusted to 0.2 parts by mass, and the amount of 184 was adjusted to 0.05 parts by mass.
[0052] Example 4
[0053] On the basis of Example 1, the amount of NVP was adjusted to 10 parts by mass, the amount of AM was adjusted to 5 parts by mass, and the amount of n-DDM was adjusted to 0.2 parts by mass.
[0054] Example 5
[0055] On the basis of Example 1, the amount of 2-EHA was adjusted to 40 parts by mass, the amount of NVP was adjusted to 5 parts by mass, the amount of AM was adjusted to 4 parts by mass, and the amount of n-DDM was adjusted to 0.2 parts by mass.
[0056] Example 6
[0057] On the basis of Example 1, the amount of 2-EHA was adjusted to 40 parts by mass, the amount of IBOA was adjusted to 10 parts by mass, the amount of ISTA was adjusted to 40 parts by mass, the amount of NVP was adjusted to 5 parts by mass, the amount of AM was adjusted to 4 parts by mass, and the amount of n-DDM was adjusted to 0.2 parts by mass.
[0058] Comparative Example 1
[0059] Step S1: 45 parts by mass of 2-ethylhexyl acrylate (2-EHA), 15 parts by mass of isobornyl acrylate (IBOA), 10 parts by mass of isooctadecyl acrylate (NVP), 15 parts by mass of hydroxyethyl acrylate (HEA), 15 parts by mass of N,N-dimethylacrylamide (DMAA), 0.6 parts by mass of 4-hydroxyvinyloxybenzophenone methacrylate (ABP), 0.2 parts by mass of n-dodecyl mercaptan (n-DDM), and 0.8 parts by mass of 1-hydroxycyclohexyl phenyl ketone (184) are heated in a water bath, nitrogen is introduced, oxygen is removed and stirred for 30 minutes to obtain a first mixture.
[0060] Step S2: Continue to introduce nitrogen into the first mixture, stir, and use UVA light with an intensity of 0.75 to 0.85 mW / cm 2 The temperature was raised to 30 °C by UV light irradiation.
[0061] Step S3: stirring in the dark, cooling to room temperature, and obtaining a prepolymerized glue having a solid content of 22% by mass;
[0062] Add 1 part by mass of modified polyolefin resin (350S), 0.2 parts by mass of benzil dimethyl ether (651), and 0.09 parts by mass of 1,6-ethylene glycol diacrylate (HDDA) to the prepolymerized glue, heat to 80°C in a dark place, stir for 30 minutes, and degas under reduced pressure to obtain OCA optical glue.
[0063] The above OCA optical adhesive was coated between a 50 μm light release film and a 75 μm heavy release film, and the UV curing energy was 2000 mJ to obtain a sheet-like OCA optical tape with a thickness of 200 μm.
[0064] Comparative Example 2
[0065] Step S1: 35 parts by mass of 2-ethylhexyl acrylate (2-EHA), 25 parts by mass of isooctyl methacrylate (EHMA), 20 parts by mass of N-vinyl pyrrolidone (NVP), 7 parts by mass of hydroxybutyl acrylate (HBA), 10 parts by mass of isostearyl acrylate (ISTA), 3 parts by mass of acrylamide (AM), 0.02 parts by mass of n-dodecyl mercaptan (n-DDM), and 0.25 parts by mass of 1-hydroxycyclohexyl phenyl ketone (184) are heated in a water bath, nitrogen is introduced, oxygen is removed and the mixture is stirred for 30 minutes to obtain a first mixture.
[0066] Step S2: Continue to introduce nitrogen into the first mixture, stir, and use UVA light with an intensity of 0.5 to 0.8 mW / cm 2 The temperature was raised to 30 °C by UV light irradiation.
[0067] Step S3: stirring in the dark, cooling to room temperature, and obtaining a prepolymerized glue having a solid content of 45% by mass;
[0068] 0.3 parts by mass of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) and 0.10 parts by mass of 1,6-ethylene glycol diacrylate (HDDA) were added to the prepolymerized glue, stirred for 30 minutes in a dark environment, and degassed under reduced pressure to obtain OCA optical glue.
[0069] The above OCA optical adhesive was coated between a 50 μm light release film and a 75 μm heavy release film, and the UV curing energy was 1200 mJ to obtain a sheet of OCA optical tape with a thickness of 200 μm.
[0070] The OCA optical tapes of Examples 1-6 and Comparative Examples 1-2 were tested. The test contents and test methods are as follows.
[0071] 180° peel adhesion test: Test conditions: temperature 23°C, humidity 65% RH; test substrate Glass A plate; sample width 25mm; speed 300mm / min; test standard ASTM D3330.
[0072] Dynamic thermomechanical analysis: Anton Paar Rheometer MCR 102e, test standard ASTM D4440-15.
[0073] Molecular weight and molecular weight distribution: gel permeation chromatograph Agilent 1260 Infinity, test standard GB / T21863-2008.
[0074] Glass transition temperature: Differential scanning calorimeter TA Q2000, test standard GB / T 19466.2-2004.
[0075] Relative dielectric constant: High and low frequency dielectric constant tester GCSTD-D, test standard GB / T11310-1989.
[0076] Light transmittance: Photoelectric haze meter NDH-2000N, test standard GB / T2410.
[0077] Gel fraction: weigh 0.3-0.5g OCA glue (m1), soak the OCA glue in EAC for 24h, filter the soaked solution with a 200-mesh filter (m2), bake the filtered filter in an oven at 150°C for 30min and weigh it (m3). The gel fraction calculation formula is: Gel = [(m3-m2) / m1]*100%.
[0078] The test results are shown in Table 1 below.
[0079] Table 1 Relevant test results of Examples 1-6 and Comparative Examples 1-2.
[0080]
[0081]
[0082] The above test results show that the dielectric constant of the OCA optical adhesive of Examples 1-6 of the present invention is low, the sensitivity of the touch screen will be improved, and the peeling force is relatively high, and it has good durability and stability. The higher storage modulus makes the OCA optical adhesive more elastic, and the ability to recover to its original state after compression is stronger. The high-pressure UV pre-curing rate is between 55% and 60%, indicating that the OCA optical adhesive has good step filling performance, and the 3500mJ high-pressure mercury lamp UV post-curing rate is greater than 70%, and the high temperature and high humidity environment test performance is good and it is not easy to produce bubbles again.
[0083] The OCA optical tape of Example 1 is subjected to aging test. The test method is as follows: Lamination: Take out two clean glass plates, apply OCA optical tape and POL in turn, then peel off the release film of OCA optical tape and the protective film of POL, and use a laminating machine for lamination. Degassing: temperature 25°C, pressure 0.6MPa, time 15min. UV curing: high-pressure mercury lamp curing, energy 3500mJ. Aging test: Put it into the corresponding aging equipment, take it out after a certain period of time, and observe the appearance. Among them: OK represents a yield of 100%, and NG represents a yield of 0%. The test results are shown in Table 2 below.
[0084] Table 2 Aging test results of Example 1
[0085]
[0086] As shown in Table 2, the OCA optical adhesive tape of Example 1 also has good anti-aging performance.
[0087] In summary, the OCA optical glue and OCA optical tape of the present invention reduce the dielectric constant of the OCA optical glue by adopting the above formula and controlling the ratio, and at the same time improve the room temperature and low temperature storage modulus of the OCA optical glue, so that the OCA optical glue itself shows good flow properties, which is conducive to step filling. In addition, the OCA glue also has good anti-aging performance, light transmittance and adhesion. The preparation method of the OCA optical glue of the present invention adopts a photopolymerization method with simple steps, which is suitable for industrial production, and the dielectric constant, light transmittance, adhesion and aging of the prepared OCA optical glue are more comprehensive.
[0088] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0089] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. An OCA optical glue, characterized in that: The components are calculated by weight percentage and include: 82%-89% of alkyl acrylates with 4-21 carbon atoms and their derivatives: 8%-15% nitrogen-containing monomers; 1.5%-1.6% hydroxyl-containing monomers; 0.04%-0.15% pre-polymerized photoinitiator; 0.17%-0.2% chain transfer agent; 0.19%-0.20% of a coating photoinitiator; and 0.14%-0.15% bifunctional crosslinking agent; the sum of the weight percentages of the components is 100%.
2. The OCA optical glue according to claim 1, characterized in that: The alkyl acrylate and its derivatives are selected from one or more of alkyl acrylates having a straight chain, alkyl acrylates having a branched alkyl chain, alkyl methacrylates having a straight chain, and alkyl methacrylates having a branched alkyl chain.
3. The OCA optical glue according to claim 1, characterized in that: The alkyl acrylate and its derivatives are selected from one or more of undecyl methacrylate, isooctyl methacrylate, 2-ethylhexyl acrylate, heptadecanyl methacrylate, isostearyl acrylate and isobornyl acrylate.
4. The OCA optical glue according to claim 3, characterized in that: The alkyl acrylate and its derivatives are a combination of 2-ethylhexyl acrylate, isostearyl acrylate and isobornyl acrylate.
5. The OCA optical glue according to claim 1, characterized in that: The nitrogen-containing monomer is selected from one or more of N,N-dimethylformamide, N-methylsuccinamide, N,2,3-trimethyl-2-isopropylbutyramide, N,N-dimethylacrylamide, 1,1-cyclohexyldiacetic acid monoamide, acrylamide, N-vinylcaprolactam, acrylonitrile, N-vinylpyrrolidone, phenoxyethyl methacrylate, triethylene glycol dimethacrylate and 4-hydroxyvinyloxybenzophenone methacrylate.
6. The OCA optical glue according to claim 5, characterized in that: The nitrogen-containing monomer is a combination of N-vinyl pyrrolidone, acrylamide and 4-hydroxyvinyloxybenzophenone methacrylate.
7. The OCA optical glue according to claim 1, characterized in that: The hydroxyl-containing monomer is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, hydroxypropyl methacrylate and 2-carboxyethyl acrylate.
8. The OCA optical glue according to claim 1, characterized in that: The pre-polymerization photoinitiator is selected from one of 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; and / or, the chain transfer agent is selected from one of n-dodecyl mercaptan, isooctyl thioglycolate and 2-mercaptoethanol; and / or, the coating photoinitiator is selected from one of isopropyl ferrocenium hexafluorophosphate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone; and / or, the bifunctional cross-linking agent is selected from one of 1,6-ethylene glycol diacrylate, N,N-methylenebisacrylamide and tripropylene glycol diacrylate.
9. A method for preparing an optical adhesive of the OCA optical adhesive according to any one of claims 1 to 8, characterized in that: include: The alkyl acrylate and its derivatives, the nitrogen-containing monomer, the hydroxyl-containing monomer, the pre-polymerization photoinitiator and the chain transfer agent are heated in a water bath, nitrogen is introduced, oxygen is removed and the mixture is stirred to obtain a first mixture; Continue to introduce nitrogen into the first mixture, stir and irradiate with a UV lamp to light-initiate and raise the temperature to 30° C.-35° C.; The mixture was stirred and cooled to room temperature in a dark environment to obtain a prepolymerized glue having a solid content of 30% to 35% by mass; Add a coating photoinitiator and a bifunctional cross-linking agent to the prepolymerized glue, stir in the dark, and degas under reduced pressure to obtain an OCA optical glue.
10. An OCA optical tape, characterized in that: include: Light release film, with a thickness of 40μm-60μm; Heavy release film, the thickness of which is 70μm-90μm; and The OCA optical adhesive layer is coated between the light release film and the heavy release film using the OCA optical adhesive described in any one of claims 1 to 8.